PHASE TRANSFORMATIONS INDUCED BY SOLID SOLUTION - Heaney P.J. (My University, 2000)
Small concentrations of impurities can create profound differences in the thermodynamic stability and the physical behavior of crystalline materials. The dramatic changes produced by chemical substitutions are perhaps best illustrated by the discovery of high-Tc superconducting oxides by Bednorz and Muller in 1986. As a pure endmember, the cuprate that revolutionized solid state physics is an insulator. However, when small amounts of Ba2+ or Sr2+ replace La3+ in La2CuO4, the doping induces a series of surprising transformations. At low levels of substitution, La2− x (Sr,Ba) x CuO4−y remains insulating, but the length scale of antiferromagnetic ordering drops precipitously. With slightly higher concentrations (~0.10 < x < ~0.18), the compound becomes a superconductor, with critical temperatures as high as 40 K for x Sr = 0.15 (Tarascon et al. 1987). In the four years that followed the announcement of Bednorz and Muller’s discovery, materials scientists pushed the superconducting critical temperature in doped cuprates beyond 100 K and published more than 18,000 papers in the process (Batlogg 1991). The systematic exploration of compositional diversity and its influence on crystal structure has long been a pursuit of materials scientists who attempt to tailor substances for specific technological applications. Geologists, by comparison, have expended much less energy on the study of impurities and their influence on transition behavior in minerals. This inattention is surprising in view of the fact that few natural materials conform exactly to their idealized compositions, and the transitional properties of “dirty” minerals may depart considerably from those of the pure endmember. For example, interstitial and/or substitutional atoms in a mineral structure can: (1) change the stability fields of polymorphs relative to each other; (2) alter the energetics of transformation between polymorphs; (3) stabilize incommensurate phases; (4) decrease the characteristic …